2021
DOI: 10.1111/ijac.13677
|View full text |Cite
|
Sign up to set email alerts
|

A new application of Hydroxyapatite extracted from dromedary bone: Adsorptive removal of Congo red from aqueous solution

Abstract: The aim of this paper is to evaluate the efficiency of the natural hydroxyapatite powder for anionic dye (Congo red) elimination from water and optimization of adsorption process parameters that are contact time (0-360 min), solution pH (4-9), initial dye concentration (400-2400 mg/l), and adsorbent dosage (0.4-20 g/l). Natural hydroxyapatite with high surface area was prepared from animal agriculture waste dromedary bone. X-ray diffraction, transmission electron microscopy, transform infrared spectroscopy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Figure 3 depicts the XRD patterns of the calcium hydroxyapatite which confirmed that HAp was obtained in weakly crystalline form. After calcination at 700 °C for 2 h, the calcium hydroxyapatite was formed as a monophasic material belonging to reference (JCPDS (76-0694)) with low crystallinity 20 22 .
Figure 3 XRD patterns of HAp dried at 100 °C and calcined at 700 °C.
…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 depicts the XRD patterns of the calcium hydroxyapatite which confirmed that HAp was obtained in weakly crystalline form. After calcination at 700 °C for 2 h, the calcium hydroxyapatite was formed as a monophasic material belonging to reference (JCPDS (76-0694)) with low crystallinity 20 22 .
Figure 3 XRD patterns of HAp dried at 100 °C and calcined at 700 °C.
…”
Section: Resultsmentioning
confidence: 99%
“…The synthetic dye Congo red (CR) is highly dissolvable in water and stable in air and light, with a complex aromatic structure; the molecular formula of CR is C 32 H 22 N 6 Na 2 O 6 S 2 . It is an anionic acid dye used in laboratories as a histological stain for amyloid, in tests of free HCl in gastric content, and as a diagnostic tool for amyloidosis [ 6 ]. The presence of one or more –N=N– groups bound to aromatic rings like benzene and naphthalene is a characteristic feature of the structure of azo dyes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These natural substrates have beneficial mechanical properties, biocompatibility, and biodegradability, making them affordable, nontoxic, and suitable for various biomedical applications 4 6 . Additionally, these unique chemical formulations could enhance the adsorptive treatment of heavy metal and dye contaminated wastewater in environmental applications 11 . Calcination, alkaline hydrolysis, precipitation, and hydrothermal are among the techniques employed to extract biogenic HA for biomedical applications 5 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%